2015
DOI: 10.1007/s10815-015-0562-7
|View full text |Cite
|
Sign up to set email alerts
|

Use of anti-mullerian hormone for testing ovarian reserve: a survey of 796 infertility clinics worldwide

Abstract: Purpose The aim of this study is to assess how anti-mullerian hormone (AMH) is used worldwide to test ovarian reserve and guide in vitro fertilization (IVF) cycle management. Methods An internet-based survey was sent electronically to registered IVF providers within the IVF-Worldwide.com network. This survey consisted of nine questions which assessed the clinics' use of AMH. The questionnaire was completed online through the IVF-Worldwide.com website, and quality assurance tools were used to verify that only o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…A survey of 796 fertility centers worldwide showed that 51% considered AMH was the best test for measuring ovarian reserve, while 40% reported AFC was the best test and only 6% selected basal FSH. However, when asked which test or factor best predicted pregnancy, the majority of centers, 80%, selected age with a small percentage selecting AMH (4%) or AFC (3%) [14]. It is imperative for providers to understand that when ordering ovarian reserve screening tests, the predictive value of these tests can be low in a younger low-risk population [15].…”
Section: Diagnosis Of Diminished Ovarian Reservementioning
confidence: 99%
“…A survey of 796 fertility centers worldwide showed that 51% considered AMH was the best test for measuring ovarian reserve, while 40% reported AFC was the best test and only 6% selected basal FSH. However, when asked which test or factor best predicted pregnancy, the majority of centers, 80%, selected age with a small percentage selecting AMH (4%) or AFC (3%) [14]. It is imperative for providers to understand that when ordering ovarian reserve screening tests, the predictive value of these tests can be low in a younger low-risk population [15].…”
Section: Diagnosis Of Diminished Ovarian Reservementioning
confidence: 99%
“…Several studies [ 1 4 ] have revealed that age, antral follicle count (AFC), and serum anti-Müllerian hormone (AMH) levels reflect the ovarian reserve admittedly, so these factors are considered valuable predictors of the ovarian response to exogenous gonadotrophins. In addition, AMH was a key for ovarian reserve-related outcomes, and has indeed been widely used in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Sixty percent of the respondents from 796 infertility clinics worldwide reported using AMH as a first-line test in in vitro fertilization (IVF) cycles, and 54% reported AMH as the best test for evaluating ovarian reserve; 89% reported that AMH results were relevant to clinical practice. [ 1 ] And AMH was an effective measure of quantitative ovarian reserve and was strongly associated with the ovarian response and oocyte yield after ovarian stimulation, [ 2 , 3 ] moreover, using AMH, AFC, and age together constituted a new model for predicting poor or excessive ovarian response. [ 4 ]…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, the AMH level declines steadily until menopause when it reaches undetectable levels [11]. To date, AMH is mostly used to predict response to in vitro fertilization therapy [12]. However, recent studies show a decline in AMH levels in CCS when compared to controls [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%